Extraction of Sodium Picrate by 3m-Crown-m Ethers and Their Monobenzo Derivatives (m = 5, 6) into Benzene: Estimation of Their Equilibrium-Potential Differences at the Less-Polar Diluent/Water Interface by an Extraction Method - Yoshihiro Kudo; Tsubasa Nakamori; Chiya Numako (Journal of Chemistry)
Individual distribution constants (KD,A) of picrate ion (Pic−) and extraction constants (Kex±) of NaPic by some crown ethers (L) into benzene (Bz) at 25°C were calculated from data reported previously. These constants were defined as KD,Pic=Pic-o/[Pic-] and Kex±=NaL+oPic-o/(Na+Lo[Pic-]), respectively. Here, the subscript “o” denotes an organic (o) phase and practically o = Bz. 15-Crown-5 ether (15C5), 18-crown-6 one (18C6), and their monobenzo (B) derivatives (B15C5 and B18C6) were selected as L. Interfacial equilibrium-potential differences (Δϕeq) at extraction were estimated at 298 K. A plot of log⁡Kex± versus -Δϕeq for the four L extraction systems gave a straight line with slope = 84 V−1. This slope was compared with those, reported before, of the dichloromethane (DCM), 1,2-dichloroethane (DCE), and nitrobenzene (NB) extraction systems. The slopes of the regression lines were in the order NB < DCM ≤ DCE < Bz. Also, the individual distribution constants of the complex ion NaL+ and an ion-pair complex (NaL+Pic-) into Bz phase were calculated from the above extraction data. At least, a comparison between these values suggests that Bz molecules mainly interact with NaL+ moiety of NaL+Pic-.